2022
DOI: 10.1158/1078-0432.ccr-22-2235
|View full text |Cite
|
Sign up to set email alerts
|

Combination of the STING Agonist MIW815 (ADU-S100) and PD-1 Inhibitor Spartalizumab in Advanced/Metastatic Solid Tumors or Lymphomas: An Open-Label, Multicenter, Phase Ib Study

Abstract: Purpose: The Stimulator of Interferon Genes (STING) is a transmembrane protein that plays a role in the immune response to tumors. Single-agent STING agonist MIW815 (ADU-S100) has demonstrated immune activation but limited anti-tumor activity. This Phase Ib, multi-center,dose-escalation study assessed the safety and tolerability of MIW815 plus spartalizumab (PDR001), a humanised IgG4 antibody against PD-1, in 106 patients with advanced solid tumors or lymphomas. Patients and methods: Patients were treated with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 37 publications
0
51
0
Order By: Relevance
“…Considering the importance of the cGAS–STING–type I IFN signaling pathway in cancer immunity, STING agonists are being developed [ 13 , 14 ]. Indeed, there are several ongoing clinical trials evaluating the efficacy of combination therapy using STING agonists in combination with anti-PD-1 antibodies on solid cancers, including melanoma [ 13 , 15 ]. In addition, recent studies have investigated whether there are existing therapies that can activate the cGAS–STING–type I IFN signaling pathway or increase the efficacy of STING agonists, with the following findings: By using melanoma, colon, and breast cancer mouse models and human cDC1 and cDC2 subsets from the peripheral blood, it was demonstrated that radiation therapy destroys tumor cells, which then release their dsDNA into the tumor microenvironment; cDC1 and cDC2 take up the dsDNA into their own cytoplasm.…”
Section: The Role Of Cgas and Sting In Immune Cells In The Tumor Micr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the importance of the cGAS–STING–type I IFN signaling pathway in cancer immunity, STING agonists are being developed [ 13 , 14 ]. Indeed, there are several ongoing clinical trials evaluating the efficacy of combination therapy using STING agonists in combination with anti-PD-1 antibodies on solid cancers, including melanoma [ 13 , 15 ]. In addition, recent studies have investigated whether there are existing therapies that can activate the cGAS–STING–type I IFN signaling pathway or increase the efficacy of STING agonists, with the following findings: By using melanoma, colon, and breast cancer mouse models and human cDC1 and cDC2 subsets from the peripheral blood, it was demonstrated that radiation therapy destroys tumor cells, which then release their dsDNA into the tumor microenvironment; cDC1 and cDC2 take up the dsDNA into their own cytoplasm.…”
Section: The Role Of Cgas and Sting In Immune Cells In The Tumor Micr...mentioning
confidence: 99%
“…Importantly, pharmacokinetic analyses revealed that MIW815 was rapidly absorbed from the injection site into the systemic circulation and had a short half-life of 24 min. Furthermore, a phase Ib dose-escalation trial of MIW815 in combination with anti-PD-1 Ab was conducted [ 15 ], in which 106 patients with advanced solid tumors or lymphomas were treated. The combination therapy was well tolerated; however, the antitumor response was minimal, and the ORR was only 10.4%.…”
Section: Sting Agonists In Clinical Trials and Next-generation Sting ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Natural STING agonists are CDNs such as c-di-GMP (CDG), c-di-AMP, and cGAMP, which have intrinsic small molecular weight, great hydrophilicity, and negative electrostatic charges. , As a result, these CDNs are difficult to cross the cellular plasma membrane and endosomal membrane to access the endoplasmic reticulum in the cytosol where STING is located. , In parallel to these cellular barriers, the susceptibility to enzymatic degradation also inhibits the delivery efficacy to target tissues, leading to poor therapeutic results. , To address these challenges, drug delivery systems have been engineered for the optimal delivery, immunomodulatory, and therapeutic efficacies of CDNs. , STING agonists have been extensively tested, most in preclinical studies, for the treatment of many types of cancers and infectious diseases. In this section, we will discuss our research on the applications of STING agonists for cancer combination immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…39,[137][138][139][140] Results of the recent clinical trials on ADU-S100 (MIW815) and MK-1454 also reaffirmed the importance of targeted immune activation and patient selection. [141][142][143] With the new knowledge in cGAS-STING signaling, we can now design of a mechanism-based [144][145][146][147][148][149][150] clinical development plan to better harness the antitumor potential of CDNs. As we look forward to seeing this new chemical modality benefiting cancer patients, we also anticipate that the chemistry-biology feedforward loop will continue to stimulate the development of new chemistry and to fuel the discovery of new biology, the two indispensable elements of drug research.…”
mentioning
confidence: 99%